Milho, amido ou caroço de algodão associados à glicerina bruta em dietas para ovinos - Perez, Henrique Leal [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this work was to evaluate the effects of the combination of crude glycerin, waste from the production of biodiesel, with the cottonseed, corn or starch on the carcass characteristics, meat, performance, ruminal parameters and production of methane gas and carbon dioxide. Were used 39 lambs contemporaries not castrated, with approximately 70 days of age and average body weight of 19 kg. The proportion roughage concentrated was 30:70. The statistical design was completely randomized with three diets and 13 replicates. There was no effect (P> 0.05) for average daily gain, with an average 0.160 kg / day, days of feedlot with an average of 101.26 days and feed conversion to 5.65. For dry matter intake effect was observed (P <0.05) reductive for diet with cottonseed. For nutrient intake effect was observed (P <0.05) for the variable intake of crude protein, acid detergent fiber and extract ethereal not having effect (P>0.05) on intake only for neutral detergent fiber. There was a significant (P<0.05) reductive digestibility of dry matter and ether extract digestibility for treatment CA and greatest digestibility for acid detergent fiber (P<0.05). Crude protein and neutral detergent fiber had no effect (P> 0.05). For the determination of ammonia nitrogen and pH, the design was used in Latin Square, triple 3x3 using nine cannulated animals in the rumen. Methane production was evaluated per in vitro incubation of the diets for 24 hours at 39°C. There was no effect (P> 0.05) to pH values of rumen fluid, with averages of 6.22; 6.26 and 6.31 for diets A, CA and M respectively. For N-NH3 concentrations were observed greatest values on the first two hours after feeding. For the production of methane gas (CH4) and carbon dioxide (CO2), there was difference (P<0.05) for the production expressed as total volume of gas, the CA diet has resulted in the lowest value. For the production of CH4 and CO2 on mL/g dry matter (DM) incubated ...

O objetivo deste trabalho foi avaliar os efeitos da associação da glicerina bruta, resíduo da produção de biodiesel, com o amido de milho, caroço de algodão ou milho sobre o desempenho, parâmetros ruminais e as características da carcaça, da carne. O experimento foi conduzido na Unidade Animal de Estudos Digestivos e Metabólicos do Departamento de Zootecnia da Faculdade de Ciências Agrárias e Veterinárias/UNESP, Campus de Jaboticabal. Foram utilizados 39 cordeiros contemporâneos não castrados, com aproximadamente 70 dias de idade e peso corporal médio de 19,08±1,5 kg. A proporção volumoso concentrado foi de 30:70. O delineamento estatístico utilizado foi o inteiramente casualizado, com três dietas e 13 repetições. Não houve efeito (P>0,05) para ganho de peso diário, com média de 0,160 kg/dia, dias de confinamento com média de 101,26 dias e eficiência alimentar de 0,183 kg,ganho/kg,MS. Para o consumo de matéria seca houve efeito (P<0,05) redutivo para o tratamento glicerina bruta associada ao caroço de algodão (CA). No consumo de nutrientes foi observado efeito (P<0,05) para as variáveis consumo de proteína bruta, fibra em detergente ácido e extrato etéreo, não tendo efeito (P>0,05) no consumo fibra em detergente neutro. Houve efeito (P<0,05) redutivo na digestibilidade da matéria seca e digestibilidade do extrato etéreo para o tratamento CA, para a fibra em detergente ácido a maior digestibilidade (P<0,05) foi observada no tratamento CA e para digestibilidade da proteína bruta e fibra em detergente neutro não houve efeito (P>0,05). Para os parâmetros ruminais, foi utilizado o delineamento em Quadrado Latino, triplo 3x3, utilizando nove animais canulados no rúmen. A produção de metano foi avaliada pela incubação in vitro das dietas durante 24 horas a 39ºC. Não houve efeito (P>0,05), para os valores de pH do líquido ruminal, com médias de 6,22; 6,26 e 6,31 para as dietas A, CA e M...
Keywords: Ovino - Carcaças; Ovino - Nutrição; Digestão; Cordeiro; Desempenho; Sheep